2016
DOI: 10.1038/srep23001
|View full text |Cite
|
Sign up to set email alerts
|

Castration influences intestinal microflora and induces abdominal obesity in high-fat diet-fed mice

Abstract: Late-onset hypogonadism (i.e. androgen deficiency) raises the risk for abdominal obesity in men. The mechanism for this obesity is unclear. Here, we demonstrated that hypogonadism after castration caused abdominal obesity in high-fat diet (HFD)-fed, but not in standard diet (SD)-fed, C57BL/6J mice. Furthermore, the phenotype was not induced in mice treated with antibiotics that disrupt the intestinal microflora. In HFD-fed mice, castration increased feed efficiency and decreased fecal weight per food intake. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
94
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 53 publications
9
94
3
1
Order By: Relevance
“…, castration or luteinizing hormone-releasing hormone analog) had not been reported to induce obesity in mice or rats 18-20 . However, our recent study showed that castration-induced obesity in C57BL/6J mice occurred in a diet-dependent manner, despite decreased food intake 16 . In general, decreased body temperature secondary to lower heat production is considered a risk for the development of obesity because of the decreased energy expenditure.…”
Section: Obesitymentioning
confidence: 90%
See 3 more Smart Citations
“…, castration or luteinizing hormone-releasing hormone analog) had not been reported to induce obesity in mice or rats 18-20 . However, our recent study showed that castration-induced obesity in C57BL/6J mice occurred in a diet-dependent manner, despite decreased food intake 16 . In general, decreased body temperature secondary to lower heat production is considered a risk for the development of obesity because of the decreased energy expenditure.…”
Section: Obesitymentioning
confidence: 90%
“…In accordance with our recent paper, 16 C57BL/6J mice were castrated at 8-weeks-old and fed the AIN93G-based standard-diet (SD, containing 7% corn oil), or the HFD (containing 14% beef tallow, 14% lard, and 2% corn oil substituted for cornstarch). Castrated mice (sacrificed at 13-weeks-old) exhibited smaller cecal content weight than sham-operated mice in the HFD-dependent manner (Fig.…”
Section: Sex Hormones and Gut Microbiotamentioning
confidence: 92%
See 2 more Smart Citations
“…Accumulating evidence demonstrates that the gut microbiota and its metabolites affect body weight and energy homeostasis (2)(3)(4). The current use of genomicsbased molecular techniques such as metabolomics and metagenomics has boosted studies aimed at clarifying the precise relation between gut microbiota and obesity (5).…”
mentioning
confidence: 99%